(untitled) (Revista Electrónica REDINE, 2018)
Research carried out in any academic or scientific field seeks to provide meaningful and benevolent contributions to any sector of society. In this sense, the cosmovisions of the protagonists involved in these inquiries must be considered at the time of carrying them out. Therefore it is important to keep in mind the different approaches, their paradigms and respective methods to be assertive when approaching the social phenomenon to study. Briefly consider the characteristics of the context, object of study, interest of the researcher and therefore its ontological, epistemological, methodological, axiological and procedural dimensions. However, these assertions mentioned at certain moments are ignored and left aside, causing inconsistency in the content developed and the data collected. In addition to the controversy and confrontation between the proponents of the quantitative and qualitative approach, which in most cases express absolute truth at the end of their research studies. Motivated by such facts, the present essay expresses some reflections of the author, who intend to contribute in disseminating the cognitive misunderstandings of this type of topic to seek to envision a consensus that provides contributions in favor of the human being and his experiences. The multiple positions taken by the inquirers must be respected, but in the same way the way of undertaking, knowing and understanding the multiple existing realities.